SPECIES IDENTIFICATION OF TRADITIONAL MEDICINE PLANTS FOR WOMEN’S HEALTH IN EAST KALIMANTAN: LESSON LEARNED FROM LOCAL WISDOM - Faiqotul Falah; Noorcahyati Hadiwibowo (Indonesian Journal of Forestry Research, 2017)
Traditional communities in East Kalimantan have been using traditional medicinal plants for centuries. This paper aims to identify the plant species used for traditional medicine for women’s health in three tribes in East Kalimantan:  Dayak Benuaq around Gunung Beratus Protection Forest, Dayak Bahau around Wehea Forest, and Kutai tribe around Kutai National Park. Medicinal plant species identification is important for plant breeding and developing utilization technology of  those species. Data were collected by: 1) interview with traditional midwives and traditional medicinal plants users in those villages; 2) collecting the medicinal plant specimens in their natural habitat; 3) qualitative analysis of  the interview records; 4) botanical identification of  the specimens in Herbarium Wanariset Samboja;  and 5) literature review about the usage of  those medicinal plants by traditional communities in other places. This research result showed 44 medicinal plant species from 30 families for cosmetics, maternal uses, and women’s reproductive health. The used parts of  the medicinal plants were the roots, leaves, barks, stem, and fruits. The medicinal plants were processed by simple methods. There were 27 species also used by other communities for similar or different efficacies, and the active chemical compounds of  25 species have been known.  The utilization of traditional medicinal plants are cheaper, more available, and accessible. However, the quality of the medicinal plants can not be guaranteed, and the dosage was not standardized. Therefore the medicinal plants need to be cultivated to ensure the quality and quantity, and to prevent species extinction.